A Produção de vídeos como estratégia pedagógica no ensino de biologia - Brito, Daniel Azevedo de (2010)
The teaching of Science, particularly of Biological science, must be able of changing the student into a critical being, who pounders his reality and participates of it. An individual capable of questioning, understanding and solving problems in a global dimension, seeing beyond the old conception of a discipline that exists by its own, ignoring the other fields of knowledge. That being said, the act of teaching must be understood within the context of the school, in a appropriate manner, not only with the mere transmission of subjects, but also with an inquisitive direction, showing to the student how to comprehend and explain his own reality. However, it is no more time for the school to stand as the only source of knowledge, for today, also television, radio, internet, videos and other data work as agents in the act of spreading the knowledge in science as much for children as for adults. In this direction, the science taught in the school plays an essential role in the education of the students, through activities that make a high level of scientific education possible. It is necessary that the students may develop a contextualized and richer scientific vocabulary, in order to better understand the presented scientific concepts. This work aims to analyze the implications of making videos as a pedagogical resource in the act of teaching biological concepts. The applied methodology was a field research, made with 36 students from the last step of high school of a school located in Fortaleza/CE, from may to September of 2009. The students produced 2 videos: a documentary and a parody. Quizzes, interviews and the observation of the environment were used as source of data. The results show that the videos made inside the school and also, specially, outside of it have an expressive potential to influence the interest of the students in learning; the videos posted in the internet are often revisited by the students; making videos outside the school was even more productive; watching videos in the internet made easier the act of learning. The final comments show that digital technologies must definitely participate of the institution. This insertion must not forget about reflection or even result in a mere technological pile up of multimedia rooms. More important than the resources is to know how to properly use these technological media, making the act of learning actually less complicated.